Major influence of plume‐ridge interaction, lithosphere thickness variations, and global mantle flow on hotspot volcanism—The example of Tristan. (29th April 2016) - Gassmöller, Rene; Dannberg, Juliane; Bredow, Eva; Steinberger, Bernhard; Torsvik, Trond H.
Abstract: Hotspot tracks are thought to originate when mantle plumes impinge moving plates. However, many observed cases close to mid‐ocean ridges do not form a single age‐progressive line, but vary in width, are separated into several volcanic chains, or are distributed over different plates. Here we study plume‐ridge interaction at the example of the Tristan plume, which features all of these complexities. Additionally, the South Atlantic formed close to where plume volcanism began, opening from the south and progressing northward with a notable decrease in magmatism across the Florianopolis Fracture Zone. We study the full evolution of the Tristan plume in a series of three‐dimensional regional models created with the convection code ASPECT. We then compute crustal thickness maps and compare them to seismic profiles and the topography of the South Atlantic. We find that the separation of volcanism into the Tristan and Gough chain can be explained by the position of the plume relative to the ridge and the influence of the global flow field. Plume material below the off‐ridge track can flow toward the ridge and regions of thinner lithosphere, where decompression melting leads to the development of a second volcanic chain resembling the Tristan and Gough hotspot tracks. Agreement with the observations is best for a small plume buoyancy flux of 500 kg/s or a low excess temperature of 150 K. The model explains the distribution of syn‐rift magmatism by hot plume material that flows into the rift and increases melt generation. Key Points: The Tristan and Gough chains can be explained by a single plume interacting with the nearby ridge The crustal thickness profile across the Walvis Ridge can be explained by a plume feeding into the southern rift part Neglecting global flow mispredicts plume excess temperature by 50 K and melt volume by 40%